Randomized controlled study to evaluate the safety and clinical impact of percutaneous auricular vagus nerve stimulation in patients with severe COVID-19 - Seitz, Tamara; Bergmayr, Franziska; Kitzberger, Reinhard; Holbik, Johannes; Grieb, Alexander; Hind, Julian; Lucny, Felix; Tyercha, Alexander; Neuhold, Stephanie; Krenn, Claus; Wenisch, Christoph; Zoufaly, Alexander; et al. (Frontiers in Physiology, 2023)
Introduction: A severe course of COVID-19 is characterized by a hyperinflammatory state resulting in acute respiratory distress syndrome or even multi-organ failure along a derailed sympatho-vagal balance. Methods: In this prospective, randomized study, we evaluate the hypothesis that percutaneous minimally invasive auricular vagus nerve stimulation (aVNS) is a safe procedure and might reduce the rate of clinical complications in patients with severe course of COVID-19. In our study, patients with SARS-CoV-2 infection admitted to the intensive care unit with moderate-to-severe acute respiratory distress syndrome, however without invasive ventilation yet, were included and following randomization assigned to a group receiving aVNS four times per 24 h for 3 h and a group receiving standard of care (SOC). Results: A total of 12 patients were included (six in the aVNS and six in the SOC group). No side effects in aVNS were reported, especially no significant pain at device placement or during stimulation at the stimulation site or significant headache or bleeding after or during device placement or lasting skin irritation. There was no significant difference in the aVNS and SOC groups between the length of stay in the intensive care unit and at the hospital, bradycardia, delirium, or 90-day mortality. In the SOC group, five of six patients required invasive mechanical ventilation during their stay at hospital and 60% of them venovenous extracorporeal membrane oxygenation, compared to three of six patients and 0% in the aVNS group (p = 0.545 and p = 0.061). Discussion: Vagus nerve stimulation in patients with severe COVID-19 is a safe and feasible method. Our data showed a trend to a reduction of progression to the need of invasive ventilation and venovenous extracorporeal membrane oxygenation which encourages further research with larger patient samples.